Pengaruh Kecemasan Bertanding Terhadap Peak Performance pada Atlet Remaja Putra Bola Basket Klub XX di Denpasar - Utami, I Gusti Agung Ayu Yunita; Sukartisih, Wayan; Angelina, Kadek Sintya (INTELEKTIUM, 2025)
This research explores the effect of competitive anxiety on peak performance among adolescent basketball athletes from XX Club in Denpasar. Competitive anxiety, often unaddressed, can significantly impair athletes' concentration, emotion regulation, and overall performance. Using a predictive correlational quantitative design, data were gathered from 42 student-athletes through standardized scales for anxiety and peak performance. Statistical analyses, including Pearson correlation and simple linear regression, revealed that anxiety significantly and positively affects peak performance (p = 0.030). Although contributing only 11.2% to performance variance, the results indicate that adaptive levels of anxiety may enhance athletes' mental preparedness. Implications for psychological training programs are discussed.